Challenges in Menstrual Management Among Women with Visual Impairments: A Study of Riryouka Kyouin with Visual Impairments in Japan - Miyono Okinaka; Tsunehiko Wada (Disabilities)
This study aimed to clarify the menstrual experiences and perceptions of women with visual impairments in Japan. An anonymous web-based questionnaire consisting of both multiple-choice (quantitative) and open-ended (qualitative) questions was administered to female Riryouka Kyouin (visually impaired teachers who provide instruction in traditional Japanese therapeutic practices—such as acupuncture, moxibustion, and massage—to students with visual impairments) employed at prefectural schools for the blind. The multiple-choice responses suggested several difficulties in menstrual management, including challenges in detecting menstrual blood, limited access to information, and concerns related to embarrassment. The open-ended responses revealed that participants, as individuals with visual impairments who also serve as educators and healthcare professionals, expressed efforts to manage menstruation appropriately in social contexts. These findings highlight the practical experiences of visually impaired women who are actively engaged in society and suggest the importance of support approaches that respect individual autonomy in managing menstruation—a bodily practice imbued with social meaning.